Radioecological investigations in the areas of fuel radioactive fallouts of the Chernobyl exclusion zone - Lypska, A. I.; Zheltonozhsky, V. A.; Nikolaev, V. I.; Shytiuk, V. A.; Kulich, N. V.; Churyumov, V. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
The isotopic composition of the radioactive contamination and the distribution of radionuclides in a soil profile are investigated. It is established that radioactivity in soil is caused mainly by 137Cs, 90Sr, 241Am and Pu isotopes, which enter the fuel matrix. The isotopic composition and the activity of fuel particles are determined. The features of radionuclides' migration in the areas of fuel fallouts in a remote post-accident period are detected. Periods of environmental semicleaning of upper soil horizons are estimated.